The Utilization of Canna Starch (Canna edulis Ker) As A Alternative Hydrocolloid on The Manufacturing Process of Yogurt Drink - Ahmad Khoirul Umam; Mei Jen Lin; Lilik Eka Radiati; Shao Yu Peng (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2018)
Yogurt as a fermented dairy product has been providing several benefits for human health and appropriate for people with lactose intolerance. Recently, the consumption level of yogurt has significantly increased. Starch can be used as an alternative hydrocolloid in the manufacturing process of yogurt. Indonesian Canna edulis Ker contains 63.27% amylopectin that has the potential used as an alternative hydrocolloid. Amylopectin has a very high capability of the water holding capacity to increase the viscosity and maintain the stability of yogurt drink. The present research was to determine the additional effects of Canna starch as an alternative hydrocolloid on the physicochemical and sensory properties of the yogurt drink during storage. Concentrations of 0.1%, 0.2%, 0.3%, and 0.4% canna starch and 0.2% CMC (control) were added to make yogurt. All treatments were carried out with four replications. Samples were refrigerated at 4oC for 24 hours and then analyzed for pH, titratable acidity, viscosity, syneresis, sedimentable fraction, and sensory properties. Data were analyzed by one way ANOVA, and followed by Duncan's multiple range test (DMRT). Data from the pH, titratable acidity, syneresis, sedimentable fraction, viscosity and sensory analyses obtained from the present study indicated that concentration of 0.1–0.4% (w/v) Canna starch could be applicable in the manufacture of the yogurt drink. Furthermore, it was found that 0.1% (w/v) of Canna starch selected as the best concentration could be used in yogurt manufacture process that resulted in similar sensory quality compared with CMC as commercial hydrocolloid.